Strongly K-nonsingular Modules - Ghawi, Tha'ar Younis (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A submodule N of a module M  is said to be s-essential if it has nonzero intersection with any nonzero small submodule in M. In this article, we introduce and study a class of modules in which all its nonzero endomorphisms have non-s-essential kernels, named, strongly -nonsigular. We investigate some properties of strongly -nonsigular modules. Direct summand, direct sums and some connections of such modules are discussed.